2013
DOI: 10.1007/s10103-012-1246-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 808 nm low-level laser therapy in exercise-induced skeletal muscle fatigue in elderly women

Abstract: Aging process involves several structural changes in muscle tissue which lead to decrease in musculoskeletal function. One of the most common physiological modifications is the increase in fatigability in elderly people, which leads to inability to maintain strength and motor control. In this context, low-level laser therapy (LLLT) has demonstrated positive results in reducing fatigue during physical exercise. Thus, this study aimed to investigate the effects of LLLT on skeletal muscle fatigue in elderly women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 35 publications
1
38
0
7
Order By: Relevance
“…The PBM parameters used in this study were based on previous studies that demonstrated positive effects of irradiation in muscle performance in older women after a fatigue protocol [24,39]. In this study, the infrared wavelength was used based on its higher penetration power compared to red wavelengths [40].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PBM parameters used in this study were based on previous studies that demonstrated positive effects of irradiation in muscle performance in older women after a fatigue protocol [24,39]. In this study, the infrared wavelength was used based on its higher penetration power compared to red wavelengths [40].…”
Section: Resultsmentioning
confidence: 99%
“…Ferraresi et al [32] observed a significant increase in muscle strength in trained irradiated healthy men measured trough the leg-press evaluation. Moreover, Toma et al [24] observed that the mean number of repetitions performed during a fatigue protocol was higher when older volunteers received active PBM in comparison to the condition using placebo irradiation. In the study, the tendency of higher 1-MR values in the laser-trained irradiated women may be related to the stimulatory effect of PBM on cellular bioenergetics and ATP synthesis, which contribute to the increased of cellular energy [16,22,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 Phototherapy has been widely used in research of different tissues, such as tendons, peripheral nerve, skin tissue, bones, and muscle. [11][12][13][14][15][16] In this context, low-level laser therapy (LLLT), and light emitting diode therapy (LEDT) are efficient on bioenergetics muscle activation, and these effects may influence performance during physical activities. Therefore, researchers started to investigate LLLT and LEDT as a way to improve muscle performance as LLLT and LEDT induce photochemical effects on cells by light absorption at photoreceptors;phenomenon described as photobiomodulation.…”
Section: Introductionmentioning
confidence: 99%
“…These modalities include massage, low intensity exercise, cryotherapy, contrast bath , hyperbaric oxygen therapy , electromyostimulation and low level laser therapy. The results on their effectiveness have not been consistent [7][8][9][10][11][12][13]. Interferential currents therapy (IFC) is one of the most commonly used electrotherapeutic modalities within the clinical practice for the management of musculoskeletal pain [14].…”
mentioning
confidence: 99%